Penerapan Model Pembelajaran Kooperatif Tipe Nht Berbantuan Media Audio Visual Untuk Meningkatkan Hasil Belajar IPA - Candra Lestari, Ni Putu (Journal of Education Action Research, 2018)
This study was aimed at finding out an increase in science learning achievement of the fourth grade students of SDN 4 Kaliuntu after implementing Audio Visual Aided - Numbered Head Together (NHT) type of Cooperative Learning model. This was a classroom action research that was done in two cycles, each consisting of planning, action, observation/evaluation and reflection. The subjects were the fourth grade students of SDN 4 Kaliuntu. The data were collected using test. The data collected were then analyzed using quantitative descriptive analysis. From the data analysis in cycle I, the average grade students science learning achievement 72,10, after being converted into criterion-referenced evaluation, the students learning achievement falls into medium level. The result of the study in cycle II showed that there was an increase in learning achievement. The average grade student science learning achievement reached 83,65, falling into a high category. The results of this study showed that the implementation of audio visual-aided NHT type of Cooperative Learning model can increase the fourth grade students’ science learning achievement in SDN 4 Kaliuntu in the academic year 2017/2018.